Dream recall frequencies and dream content in Wilson’s Disease with and without REM sleep behaviour disorder: a neurooneirologic study - Tribl, Gotthard; Schredl, Michael (Behavioural neurology, 2016)
Objective. Violent dream content and its acting out during rapid eye movement sleep are considered distinctive for rapid eye movement sleep behaviour disorder (RBD). This study reports first quantitative data on dreaming in a cohort of patients with treated Wilson’s disease (WD) and in patients with WD with RBD. Methods. Retrospective questionnaires on different dimensions of dreaming and a prospective two-week home dream diary with self-rating of emotions and blinded, categorical rating of content by an external judge. Results. WD patients showed a significantly lower dream word count and very few other differences in dream characteristics compared to age- and sex-matched healthy controls. Compared to WD patients without RBD, patients with WD and RBD reported significantly higher nightmare frequencies and more dreams with violent or aggressive content retrospectively; their prospectively collected dream reports contained significantly more negative emotions and aggression. Conclusions. The reduction in dream length might reflect specific cognitive deficits in WD. The lack of differences regarding dream content might be explained by the established successful WD treatment. RBD in WD had a strong impact on dreaming. In accordance with the current definition of RBD, violent, aggressive dream content seems to be a characteristic of RBD also in WD.